EKO-EDUKASI PENANAMAN POHON DAN KEMANFAATANNYA UNTUK EKOSISTEM LINGKUNGAN BAGI SISWA PENDIDIKAN DASAR - Bokiraiya Latuamury; Moda Talaohu; John F Sahusilawane (Universitas Nusa Bangsa, 2024)
The tree planting program aims to maintain environmental balance and sustainability to create environmental health and balance the present and future water systems. The tree planting eco-education program is an environmental education effort that has become a popular community movement. This Community Service Program (PKM) aims to increase awareness of 9-year primary education students, especially elementary school students. The extension method uses simple teaching aids in short videos and presentations containing children's animated images regarding tree planting eco-education and its benefits for environmental sustainability, especially water management on the small islands of Maluku Province. The PKM solution measures primary education students' knowledge and attitudes regarding tree planting and its benefits in maintaining partner areas' environmental ecosystem and water management (hydro-orological system). The results of the assessment criteria for students' knowledge and attitudes regarding tree planting and its benefits for the environmental ecosystem are included in the medium category. The expected result of the PKM program is that it can educate students at SD Negeri 300 Central Maluku to improve the knowledge and attitudes of students in the middle category who are increasing in partner areas. Keywords: benefits of tree planting, small island, elementary school students, water management Abstrak Program penanaman pohon merupakan upaya menjaga keseimbangan dan kelestarian lingkungan guna mewujudkan kesehatan lingkungan dan menyeimbangkan tata air masa kini dan masa depan. Program eko-edukasi penanaman pohon merupakan sebuah upaya pendidikan lingkungan yang menjadi gerakan komunitas yang populer. Program Pengabdian Kepada Masyarakat (PKM) ini bertujuan untuk meningkatkan penyadartahuan siswa pendidikan dasar 9 tahun terutama siswa Sekolah Dasar. Metode penyuluhan menggunakan alat peraga sederhana berupa video singkat dan presentasi yang berisi gambar animasi anak mengenai eko-edukasi penanaman pohon dan kemanfaatannya bagi kelestarian lingkungan dan khususnya tata air di pulau kecil Provinsi Maluku. Solusi PKM yang ditawarkan adalah mengukur pengetahuan dan sikap siswa pendidikan dasar mengenai penanaman pohon dan kemanfaatannya dalam menjaga ekosistem lingkungan dan tata air (sistem hidro-orologi) wilayah mitra. Hasil penilaian kriteria untuk pengetahuan dan sikap siswa mengenai penanaman pohon dan kemanfaatannya bagi ekosistem lingkungan termasuk dalam kategori sedang. Hasil yang diharapkan dari program PKM adalah program PKM ini dapat mengedukasi siswa SD Negeri 300 Maluku Tengah meningkatkan pengetahuan dan sikap siswa-siswi yang kategori sedang semakin meningkat di wilayah mitra. Kata Kunci: kemanfaatan penanaman pohon, pulau kecil, siswa sekolah dasar, tata air